Visualization of facet-dependent pseudo-photocatalytic behavior of TiO2 nanorods for water splitting using In situ liquid cell TEM. (August 2019) - Yin, Zu-Wei; Betzler, Sophia B.; Sheng, Tian; Zhang, Qiubo; Peng, Xinxing; Shangguan, Junyi; Bustillo, Karen C.; Li, Jun-Tao; Sun, Shi-Gang; Zheng, Haimei
Abstract: We report an investigation of the pseudo-photocatalytic behavior of rutile TiO2 nanorods for water splitting observed with liquid cell transmission electron microscopy (TEM). The electron beam serves as a "light" source to initiate the catalytic reaction and a "water-in-salt" aqueous solution is employed as the electrolyte. The observation reveals that bubbles are generated preferentially residing near the {110} facet of a rutile TiO2 nanorod under a low electron dose rate (9.3–18.6 e - /Å 2 ·s). These bubbles are ascribed to hydrogen gas generated from the pseudo-photocatalytic water splitting. As the electron beam current density increases to 93 e - /Å 2 ·s, bubbles are also found at the {001} and {111} facets as well as in the bulk liquid solution, demonstrating the dominant effects of water electrolysis by electron beam under higher dose rates. The facet-dependent pseudo-photocatalytic behavior of rutile TiO2 nanorods is further validated using density functional theory (DFT) calculation. Our work establishes a facile liquid cell TEM setup for the study of pseudo-photocatalytic water splitting and it may also be applied to investigation of other photo-activated phenomena occurring at the solid-liquid interfaces. Graphical abstract: Photocatalytic water splitting using TiO2 as the active catalyst has been studied intensively. Although facet-dependent photocatalytic properties of TiO2 nanostructures was speculated, it has not been directly observed. Here, we visualized the facet-dependent pseudo-photocatalytic water splitting using a liquid cell TEM setup. Using a low dose electron beam as the "light" source and a "water-in-salt" aqueous solution, the preferential hydrogen bubble generation near the {110} facets of a TiO2 nanorod was observed.Image 1 Highlights: Established a facile liquid cell TEM setup for in situ study of "photo" catalytic water splitting. The generated H2 bubbles preferentially reside near the {110} facets of a rutile TiO2 nanorod. The electron beam was used as a "light" source to initiate the catalytic water splitting. A "water-in-salt" solution and low electron dose suppressed direct water electrolysis by e-beam. A lower work function of the TiO2 {110} facets from DFT calculations validates the observation.